Toward an Understanding of Religious Tolerance: Quest Religiousness and Positive Attitudes Toward Religiously Dissimilar Others - Van Tongeren, Daryl R. (The international journal for the psychology of religion, 2016)
We interact frequently with individuals with religious beliefs that vary from our own. Although we may naturally prefer interacting with religiously similar others, individuals vary in their attitudes toward religiously dissimilar others. In the present set of studies, we examined how variability in quest religiousness affects religious tolerance. In Study 1 (N = 159), we found that quest religiousness in Christian undergraduates was associated with positive attitudes toward both non-Christian religious groups and atheists. In Study 2, 118 Christian undergraduates evaluated vignettes regarding a devout moral or an average morality Christian (ingroup) or Muslim (outgroup). Participants preferred moral targets relative to less moral targets. However, when rating moral targets, participants high in quest religiousness preferred the Muslim target (religious outgroup member), whereas those low in quest religiousness preferred the Christian target (religious ingroup member). We discuss implications for the links between quest religiousness and religious tolerance.